Developing a quantitative research method on planned obsolescence in architecture - Akyurek, K. B.; Ciravoglu, A. (IOS PRESS, 2017)
Planned obsolescence, a developed theory to maintain the continuity of production by consuming, manifests itself in a large number of products since its first emergence. Through the use of substandard materials, the short-lived products ensure rapidity and continuity in consumption. Additionally, the newer and different options awaken desire of consumers to change their 'obsolete' products. Thus, planned obsolescence becomes both a trigger and a consequence of the consumer society. In contrast to broad discussions on the scheduled lifespan of the products in economics and industrial design, a very small number of studies focus on the building lifetimes. Indeed, planned obsolescence is also a problem of architecture but surely has been carried within a different process and approach than with industrial products. The initial aim of this study is to point out the existence of planned obsolescence in architecture by exposing the ambiguity behind the determination of building demolitions (in other words consciously defined 'expiration dates'). In the framework of the paper, an ongoing urban transformation project in Istanbul: Tarlabasi Renewal project is examined as a case study. By doing so, the crucial variables that have effects on economic existences of the buildings are underlined in the specific case. Due to the constitution of a basic equation, this study tries to demonstrate the possibility of a developing quantitative research method on building lifetimes in replace of stereotypical assumptions. Consequently, it is envisioned that the subjectivity concerning the demolitions of buildings shall be controlled with the determination of prominent factors and their ratios in overall.
Keywords: Planned obsolescence; Building lifetimes; Demolitions; Urban transformation; Tarlabasi Renewal Project; Business & Economics; Science & Technology - Other Topics